Selective Mutism and Comorbidity with Specific Learning Disorders: Evaluation and Multimodal Intervention in a Clinical Case of a Female Child from 7 to 11 Years of Age - Micaela Capobianco; Alberto Costa (MDPI AG, 2024)
Selective mutism (SM) is an anxiety disorder that is characterized by a child's persistent inability to communicate verbally in some or all contexts of social life. It is often associated with other cognitive-affective disorders. Performing cognitive-behavioral assessments and psychological interventions can be challenging due to the difficulty in administering standardized neuropsychological tests and involving family and teachers in the intervention program. In a single case study, a young Filipina girl with SM underwent a comprehensive neuropsychological assessment and received multimodal therapeutic intervention between the ages of 7 and 11. The psychological intervention included cognitive-behavioral psychotherapy to improve social-cognitive skills and learning abilities, reduce anxiety, and provide speech therapy. The parents and teachers were actively involved in the therapeutic process and a underwent a psycho-education program. Following this treatment, at the age of 11, the girl started verbalizing in therapy and school contexts, although she still used non-verbal strategies. There was also a gradual improvement in her communicative-linguistic skills and school learning. In conclusion, this report emphasizes the importance of applying an integrated and multimodal intervention to treat SM in children, including psychoeducation for parents and teachers.